(untitled) (Global Journal of Medical Research, 2014)
Reduction in circulating platelets is observed relatively frequently in cases of malaria due to P. vivax. 61 patients with confirmed vivax malaria were enrolled in this study and the platelets were counted by hematological analyzer. our study revealed that 77.1% had platelets count less than 150,000/ µl , thrombocytopenia grade 1 represent 43%, grade 2 represent 19.8%, grade 3 represent 9.8% and grade 4 represent 4.9%. Thrombocytopenia should be a consideration as a clue to the presence of malaria in endemic region.